Tathbiq Madkhal al-Ta’lim wa al-Ta’allum al-Siyaaqi fi Ta’lim al-Lughat al-Arabiyah bi Istikhdaam kitaab "al-Arabiyah al-Sahlah" li Thulaab Jami’ah al-Qaadiry al-Islamiyah Jember li as-Sanah al-Diroasiyah 2021/2022 - Elok Rufaiqoh; Hasyim Asy'ari (Lugawiyyat, 2022)
The objectives of this research are to describe the planning, implementation and evaluation of the application of contextual learning and teaching approach in teaching Arabic for students of Al-Qodiri Islamic University, Jember. The research methodology is using the qualitative method. And data collection methods using observation, personal and documentary interview. The results of this research are that the application of contextual teaching and learning approach in teaching Arabic is well done. It starts with planning the lesson plan and then the teacher gives the plan to the students to discuss it with them. As for the implementation of this approach in the teaching of the Arabic language, it contains the introduction and the presentation in which the teacher applies the elements of the entrance to teaching and contextual learning in the teaching and learning process, which are: Constructivism, the process of discovery and discovery, questioning, the educated society, modeling, and the reflected image. And the last is the conclusion, meaning evaluation in teaching Arabic, with appropriate tests and tested skills.